Galectin-3 organizes histological compartments associated with inflammatory reaction induced by gliadin in BALB/c mice - PAULA C.P. SILVA; VICTOR F.S. FERREIRA; NATÁLIA G. MAÇÃO; RAFAEL M.S. LIMA; FELIPE S. LEMOS; FELIPE L. OLIVEIRA (Anais da Academia Brasileira de Ciências)
Abstract Galectin-3 regulates cell-cell and cell-extracellular matrix interactions in distinct tissues, including intestinal epithelial cells interfering with inflammatory responses. In the gut, galectin-3 stabilizes epithelial junctions and intestinal permeability. Here, it was investigated whether gliadin (protein of gluten) can induce inflammatory reactions in the digestive system in the presence or absence of galectin-3. BALB/c wild-type (Lgals3+/+) and genetically mutated in LGALS3 (Lgals3-/-) mice were divided into controls (water) or orally supplemented with gliadin (100mg/day) for 30 days. Fragments of duodenum, jejunum, ileum, colon and rectum were processed for histological analysis and immunohistochemistry. Gliadin induced an inflammatory response in the gut of Lgals3+/+ and Lgals3-/- mice, but with high severity in the Lgals3-/- mice. Galectin-3 was significantly expressed by enterocytes in all fragments. However, it was drastically reduced after gliadin supplementation and directly associated with severe inflammation in all compartments of the gut. In parallel, gliadin supplemented Lgals3-/- mice showed significant inflammatory signals in the mucosa, including leukocyte infiltration in mucosal sites, hyperplasia of crypts, enhance of intraepithelial lymphocytes, and hypertrophy linked to accumulation of apoptotic bodies in the Peyer’s patches. These data suggested that galectin-3 plays protective roles in the gut submitted an inflammatory stress after gluten intake.